Use of Medicinal Plants with Teratogenic and Abortive Effects by PregnantWomen in a City in Northeastern Brazil - Cristina Ruan Ferreira de Araújo; Felipe Gomes Santiago; Marcelo Italiano Peixoto; José Olivandro Duarte de Oliveira; Mayrla de Sousa Coutinho (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Purpose The purpose of this study is to verify the use ofmedicinal plants by pregnant women treated at four Basic Health Units and at a public maternity facility in Brazil s northeast. Methods This is a cross-sectional, quantitative study, performed between February and April 2014. The subjects were 178 pregnant women, aged 18 to 42 years. To collect data, a structured questionnaire with dichotomous and multiple choice questions was used. To verify the correlation between the variables, Pearson s chi-square test was used. Results The study showed that 30.9% of the pregnant women used medicinal plants, and boldo was the most cited (35.4%). All the plants utilized, except lemongrass, have toxic effects in pregnancy, according to Resolution SES/RJ N° 1757. There was no statistically significant correlation between social class and use of medicinal plants. Conclusion The health of the study participants and their unborn children is at risk due to the inappropriate use of medicinal plants.